Unveiling the Shadows: Understanding Urban Perspectives on Cervical Cancer - Sheetal Mahendher; Leonard L; Aprajitha R (Talenta Publisher, 2026)
Background: Cervical cancer remains a significant public health concern in India, including urban regions like Bangalore, where awareness of HPV and its vaccination is still limited. Despite the availability of effective vaccines, uptake remains low due to misinformation, stigma, and inadequate health education. Objective: This study aims to assess the awareness, perceptions, and acceptance of cervical cancer vaccination among individuals aged 18 and above in Bangalore South, and to identify key barriers influencing vaccination uptake. Methods: A quantitative, inductive research approach was employed using a structured survey administered to 51 purposively selected participants. The survey captured awareness of HPV, vaccination, Pap smear screening, and prevalent myths. Descriptive statistics and Pearson’s chi-square tests were conducted using SPSS to examine associations between demographic factors and vaccine-related attitudes. Results: Findings revealed substantial gaps in awareness and several misconceptions regarding HPV and vaccination. Chi-square results indicated no significant associations between awareness levels and age, gender, or income, while education showed a significant relationship with perceived vaccine safety. Conclusions: Despite urban residency, awareness and uptake of cervical cancer vaccination remain low. Targeted education, myth-busting campaigns, and improved accessibility are crucial to enhancing vaccination acceptance and preventing cervical cancer in urban communities.